Inovasi Pelayanan Publik Bupati Ngantor Di Desa (BUNG DESA) Kabupaten Labuhanbatu Utara - Setiadi; Sigiro, Benny (Program Studi Administrasi Negara Universitas Serang Raya, 2024)
Difficult road access and long travel distances in several areas of Labuhanbatu Utara Regency have become the main obstacles for the community in obtaining public services. In response to this issue, the Head of the Labuhanbatu Utara District launched an integrated service innovation through the